Needle Stick Injuries among Healthcare Workers in a Tertiary Care Hospital of Lucknow - Prabhat K Pandey; Rajesh Kunwar; Mili Sengar; Ginic Gupta; Rama Saini (Indian Association of Preventive and Social Medicine, 2024)
Introduction: In healthcare settings, needle stick injuries (NSIs) pose a serious risk to occupational health. They often go unreported, which exposes a crucial weakness in workplace safety procedures. Research on needle stick injuries is crucial for enhancing the safety and well-being of healthcare workers, improving healthcare delivery, and ensuring that healthcare environments are as safe and effective as possible. Objectives: To determine the prevalence and associated factors of needle stick injuries among Healthcare workers in a Tertiary Care Hospital in Lucknow. Method: A cross-sectional study was conducted from April 2024 to June 2024 in a tertiary care hospital, Lucknow, Uttar Pradesh among 213 Health Care Workers (HCWs) i.e., physicians (consultants, specialists, and residents), nurses, other healthcare workers, and class IV employee working for a period of more than one year. A pre designed and pre tested structured questionnaire was developed for the study. Data regarding injuries by needle stick was collected. All needle stick injuries occurring between the period April 2023 and March 2024 was recorded. Results: The prevalence of needle stick injuries among healthcare workers was found to be 11.7% (25 out of 213) in the period of April 2023 to March 2024. Fingers (88%) were the most common site of NSI, followed by palm (8%) and hands (4%). The most common place of occurrence of NSI was wards (40%) and majority of the injuries were superficial (84%). The most common sharp causing NSI was needle (72%), followed by glass items (20%) and scalpel (4%). There was a statistically significant association between NSI and gender, years of experience, dissembling of needles by hand and working shift of health care workers (p=0.000). Conclusion: Prevalence of NSI was found to be higher among medical and paramedical staff who were working during day shift, working more than 7 hours a day and had an experience of less than 3 years.